Хронологічні горизонти Броньківського замку - Калініченко, Віталій; Прохненко, Ігор (Ужгород, Вид-во УжНУ «Говерла», 2018)
Within last decade a significant increase in number of field archeological studies of medieval and early modern times’ sites is evident in Zakarpats’ka oblast of Ukraine. The medieval and early modern group of expedition of Uzhhorod National University, led by Igor Prokhnenko, scientists’ main attention has been drawn to study of fortified points in Vynohradiv, Korolevo, Serednye, Bron’ka, Kovaszo, Siltse, Visk, and Chynadievo. The castle of Bronka is located near the village of Bronka, Irshava district of Zakarpats’ka oblast of Ukraine, is distinguished by earliest finds. The history of the castle is well represented in the scientific literature. However there are only few publications of actual facts proven by data from the written sources. Stone-made fortifications had been raised at the second part of XIII century. In spite of very interesting history of the castle, only irregular minor archeological studies took place on the site and its surroundings in the past. Since 2008 expedition of Uzhhorod National University started studying. Two excavation sites have been set up in central part of the monument. The depth of the cultural layer varied from 0.5 to 1.0 m. A collection of materials has been found during the works, in particular: fragments of ceramic utensils, bone and metal products. The general dating of the finds is the end of XIII – XV centuries. Castle’s inventory review, it is worth to mention that analysis of both stratigraphic situation. Among pre-castle materials of Bronka, the little layer of the copper-bronze period, which had not been described in scientific literature, was discovered. Main party of discovered finds suggests operation of fortifications from the end of XIII until start of XIV centuries. The castle in Bronka has been used as a controlling one at XV century. This dating does not contradict the written sources. Analysis of a large number of written sources will provide additional information and specify the history of this key fortification in Zakarpats’ka oblast of Ukraine.
The chronological horizons of Bronka castle
Keywords: Бронька; замок; письмові джерела; археологічні дослідження; датування; кераміка; монета; зброя